2006
DOI: 10.5194/acp-6-2355-2006
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning between the inorganic chlorine reservoirs HCl and ClONO<sub>2</sub> during the Arctic winter 2005 from the ACE-FTS

Abstract: Abstract. From January to March 2005, the Atmospheric Chemistry Experiment high resolution Fourier transform spectrometer (ACE-FTS) on SCISAT-1 measured many of the changes occurring in the Arctic (50-80 • N) lower stratosphere under very cold winter conditions. Here we focus on the partitioning between the inorganic chlorine reservoirs HCl and ClONO 2 and their activation into ClO. The simultaneous measurement of these species by the ACE-FTS provides the data needed to follow chlorine activation during the Ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…This winter was chosen, because it was characterized by an unusually large catalytic ozone loss as documented in numerous studies (e.g., Dufour et al, 2006;Grooß and Müller, 2007;Singleton et al, 2007Singleton et al, , 2005Rösevall et al, 2008;Rex et al, 2006). Comparison with previous studies for the other winters will be described later in this section.…”
Section: Arctic Wintersmentioning
confidence: 99%
“…This winter was chosen, because it was characterized by an unusually large catalytic ozone loss as documented in numerous studies (e.g., Dufour et al, 2006;Grooß and Müller, 2007;Singleton et al, 2007Singleton et al, , 2005Rösevall et al, 2008;Rex et al, 2006). Comparison with previous studies for the other winters will be described later in this section.…”
Section: Arctic Wintersmentioning
confidence: 99%
“…Hence, by the end of Arctic winter, high values of more than 2 ppbv ClONO 2 have been measured (see, e.g., Dufour et al, 2006;Höpfner et al, 2007;Wetzel et al, 2010).…”
Section: G Wetzel Et Al: Diurnal Variations Of Reactive Chlorine Anmentioning
confidence: 99%
“…8. ClONO 2 values of up to 1.5 ppbv, which are not unusual for mid-winter conditions (Dufour et al, 2006), were measured at 27 km. However, below 25 km ClONO 2 mixing ratios fall to values below 0.1 ppbv, coincident with the region of high ClO x amounts.…”
mentioning
confidence: 99%
“…The fitting error of the ClONO 2 data is below 10 % at 20-30 km and increases to 40 % at 14 km . Dufour et al (2006) have provided an error budget for a single occultation: the total errors for HCl and ClONO 2 are, respectively, estimated to be 4-7 % and 10-19 % between 16.5 km and 28.5 km. et al, 2009, 2013).…”
Section: Ace-ftsmentioning
confidence: 99%
“…An aircraft mission was performed in the 1999/2000 Arctic winter; the time evolution of the Cl y species has been investigated (e.g., Wilmouth et al, 2006). Dufour et al (2006) also showed an evolution of the Cl y partitioning in the 2004/2005 Arctic winter from the Atmospheric Chemistry Experiment-Fourier Transform Spectrometer (ACE-FTS) measurements. However, the HCl value or HCl / Cl y ratio in the Arctic was lower than those in the Antarctic (e.g., Santee et al, 2008b;Manney et al, 2011;Wegner et al, 2012), even with severe ozone loss in the 2010/2011 Arctic winter (e.g., Manney et al, 2011).…”
Section: Introductionmentioning
confidence: 99%